2020
DOI: 10.1186/s12879-020-05538-x
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Management of Oligosymptomatic Patients with respiratory infection in the era of SARS-CoV-2: Experience from rural German general practitioners

Abstract: Background Covid-19 is causing a pandemic and forces physicians to restructure their work. We want to share our experience in the outpatient management of potentially-infected patients with special consideration of altered national test strategies during the crisis. Methods We analysed patients with respiratory symptoms reporting to our three rural general practitioner (GP) offices in North Rhine-Westphalia, Germany, from 27.01–20.04.2020 (n = 489 from a total of 6090 patients). A history of symptoms was tak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As Germany has a federated and self-governing system in the healthcare sector with 17 self-regulatory regional organization for the outpatient sector, clear division of responsibilities was often absent [ 21 ]. Many physicians complained about a general, long-lasting shortage of PPE [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Germany has a federated and self-governing system in the healthcare sector with 17 self-regulatory regional organization for the outpatient sector, clear division of responsibilities was often absent [ 21 ]. Many physicians complained about a general, long-lasting shortage of PPE [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting question; to that direction, we decided to include family members (father, mother, and sister of one patient) and individuals working together or living in the same house. We consider this a vital reporting aspect in establishing guidelines for sequential testing, managing oligo- or asymptomatic patients in outpatient settings, and informing future clinical study design across settings, as highlighted by a recent report [ 33 ]. The median incubation period of five days (even of approximately four and three days for the Delta and Omicron variants, respectively) creates a false sense of safety but also presents a challenge in terms of study inclusion and proper trial conduct and reporting [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rural primary care physicians in Germany re-organised their practices to screen and triage patients, as well as managing patients remotely by telephone or video. They also observed a higher probability for more severe disease in COVID-19 patients in rural areas [117,118]. In China, one study reported that primary care practitioners took on key public health roles of tracing, screening, and educating in rural areas [119].…”
Section: Role Of Digital Technologymentioning
confidence: 97%